Monographs on fragrance raw materials - Opdyke, D. L. J. (Published on behalf of the Research Institute for Fragrance Materials by Pergamon Press, 1979)
Monographs on Fragrance Raw Materials contains a collection of monographs originally appearing in Food and Cosmetics Toxicology from the first issues in 1973 to the last ones in 1978. The monographs are organized in alphabetical order, as a regular feature of Food and Cosmetics Toxicology. This monograph will prove valuable to many readers of Food and Cosmetics Toxicology, as well as to the wider community of scientists and interested consumers.